Perihal Hukum Material Perkawinan Di Indonesia Pra Perkawinan - Hafidhul Umami (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
Giving a dowry (mahar) is part of the principles in marriage law. The dowry must be given by the groom to the prospective bride in a form agreed upon by both parties. The dowry is often interpreted as a gift or offering. It is preferred that the dowry is simple and does not burden the prospective spouse, considering that the real essence of marriage lies in the life after the marriage ceremony. The dowry is not considered a fundamental requirement of marriage. According to the Indonesian Compilation of Islamic Law (KHI), the dowry is defined as a gift. It can take various forms, such as money, goods, or services, as long as it does not contradict Islamic law. The principles of marriage are as follows: a. Voluntary principle, b. Principle of consent, c. Principle of free choice.